The (M) other’s Voice: Representations of Motherhood, Childhood, and Human Capital Sustainability in Kamala Markandaya’s Nectar In A Sieve (Journal of the College of Education for Women, 2024)
Mother-daughter relationships have long captivated female writers, serving as a lens to explore the intricate bonds of intimacy, conflict, and identity. Kamala Markandaya’s Nectar in a Sieve (1954) stands as a seminal work in contemporary Indian literature, offering a profound exploration of motherhood and childhood against the backdrop of rural colonial India’s socio-economic struggles. This article employs feminist literary theory to analyze how Markandaya portrays the roles, agency, and resilience of women and children within a patriarchal and economically oppressive context. The novel’s depiction of maternal figures reveals the multifaceted challenges of motherhood, encompassing both nurturing and survival in a rapidly changing world. By intertwining personal narratives with broader socio-political realities, Markandaya enriches the discourse on maternal identity, illustrating how mothers navigate systemic inequities while safeguarding family well-being. Central to this exploration is Marianne Hirsch’s concept of the “double voice,” which calls for a dual narrative approach in women's writing. This methodology allows Markandaya to intertwine the personal and collective dimensions of women’s experiences, bridging the gap between individual struggles and societal critique. Furthermore, the novel foregrounds the interdependence of childhood and human capital sustainability, demonstrating how children’s futures are shaped by their mothers’ sacrifices and resilience. By situating maternal voices within this socio-economic framework, the novel critiques colonial structures while advocating for the recognition of women’s roles as agents of cultural and economic sustenance. This study underscores Nectar in a Sieve’s enduring relevance, offering a nuanced perspective on motherhood, survival, and systemic resistance in postcolonial literature.